Transfusion Camp: a prospective evaluation of a transfusion education program for multispecialty postgraduate trainees. Issue 6 (4th April 2019) - Lin, Yulia; Tilokee, Everad; Chargé, Sophie; Alam, Asim; Cserti‐Gazdewich, Christine; Lau, Wendy; Lee, Christie; Lieberman, Lani; Nixon, Paula; Owens, Wendy; Pavenski, Katerina; Pendergrast, Jacob; et al.
Abstract : BACKGROUND: The optimal method of providing transfusion medicine (TM) education has not been determined. Transfusion Camp was established in 2012 at the University of Toronto as a centrally delivered TM education program for postgraduate trainees. The impact of Transfusion Camp on knowledge, attitudes, and self‐reported behavior was evaluated. METHODS: Didactic lectures (delivered locally, by webinar, or recorded) and locally facilitated team‐based learning seminars were delivered over 5 days during the academic year to 8 sites: 7 in Canada and 1 in the United Kingdom. Knowledge assessment using a validated 20‐question multiple‐choice exam was conducted before and after Transfusion Camp. Attitudes and self‐reported behavior were collected through a survey. RESULTS: Over 2 academic years (July 2016 to June 2018), 390 trainees from 16 different specialties (predominantly anesthesia, 41%; hematology, 14%; and critical care, 7%) attended at least 1 day of Transfusion Camp. The mean pretest score was 10.3 of 20 (±2.9; n = 286) compared with posttest score of 13.0 (±2.8; n = 194; p < 0.0001). Lower pretest score and greater attendance (4–5 days compared with 1–3 days) were associated with larger improvement in posttest score; delivery format, specialty, and postgraduate year were not. Trainees reported an improvement in self‐rated abilities to manage TM scenarios; 95% rated TM knowledge as very or extremely important in providing patient care; and 81% indicated that they had applied learning from Transfusion Camp into clinical practice. CONCLUSIONS: Transfusion Camp increased TM knowledge, fostered a positive attitude toward TM, and enabled a self‐reported positive impact on transfusion practice in postgraduate trainees. It is a novel and scalable approach to delivering TM education.